The physical preparation and testing in elite youth wrestling in Albania - Kapedani, Kujtim; Bulku, Altin (Edelweiss Applied Science and Technology, 2025)
The Success of Albanian Wrestling: We will address the general and special physical condition of our young wrestlers according to the demands of the current times and our wrestling sport. This study focuses on organizing and implementing an active and specific training methodology aimed at the complex development and progressive rhythms of the training indicators for young wrestlers. It includes the creative processing of positive experiences, which is accompanied by systematic analytical activity and the constructive processing of a wide range of contemporary literature. The study presented is the product of an experimental process organized with athletes from our national wrestling team for youth. Data processing was carried out using SPSS27. F.max relative: This is the maximum relative strength. P.max.rel/p/kg: This is the relative power per kg/body weight. The duration of the support with both feet on the ground is crucial; the faster it is completed, the better. The complex, dynamic, standardized, and overload-free training increases the physical, movement, and functional standards of the wrestlers. The content of training units should emphasize special and specific elements, supplemented with exercises for strength, speed, and coordination. The training activity should be based on the structure of ’macro-cycles.’